All Questions Topic List
None Questions
Previous in All Question Next in All Question
Previous in None Next in None
Question Number 170150 by daus last updated on 17/May/22
Answered by Rasheed.Sindhi last updated on 17/May/22
m2=n+2..........(i)n2=m+2...........(ii)4mn−m3−n3=?(i)−(ii):m2−n2=−(m−n)(m−n)(m+n)=−(m−n)(m−n)(m+n)+(m−n)=0(m−n)(m+n+1)=0m=n★∣m+n=−1(i)+(ii):m2+n2=m+n+4(m+n)2−2mn=m+n+4(−1)2−2mn=−1+4=3mn=−14mn−(m3+n3)=4mn−(m+n)3+3mn(m+n)=4(−1)−(−1)3+3(−1)(−1)=−4+1+3=0★m=n(i)⇒m2−m−2=0m=n=1±1+82=1±32=2,−14mn−m3−n3=4m2−m3−m3=2m2(2−m)={2(2)2(2−2)=02(−1)2(2+1)=6
Commented by peter frank last updated on 19/May/22
thanks
Terms of Service
Privacy Policy
Contact: info@tinkutara.com